Place of Mursal hadith in Hanafi's mazhab (Journal of Philosophy Culture and Political Science, 2015)
The article deals with questions about Mursal hadith, which is acceptable in times were companions (Sahaabah), representatives of the generation of followers (Taabi'een) and had seen Taabi'een (atbaut-Taabi'een) despite the fact that the actions and the conditions for the adoption of such hadith were different. In four schools, Mursal hadith could be used as evidence. Many of the Hadith scholars, and even those who are kind to the chain of transmitters were taken out, Mursal hadith transmitted by the most authoritative and well-known Taabi'een, to the rank of authentic (Sahih) Hadith. Since Abu Hanifa (peace be upon him) was Taabi'een applying them Mursal hadith, as evidence it was quite natural. Abu Hanifa predominantly feature was the fact that he had an opportunity to address not only Taabi'een and atbaut Taabi'een-on application-Mursal hadith, but he could personally testify for the actions listed in these hadiths to support their contents.
Keywords: Hanafi; Abu Hanifa; mursal hadith; hadith Musnad; Taabi'een; the Sahabah; atbau Taabi'een.